Philosophical problems of the mentalistic logic - Петік, Я. (Київський національний університет імені Тараса Шевченка, 2019)
Paper deals with philosophical problems of mentalistic logic. Mentalistic logic is a formal system that concentrates on underpinning processes of mental life instead of certain elements of extrinsic rational behavior as most of existing logics (like BDI calculi) do. The project is compared to the existing logics of actions. Mentalistic logic is patually a formal system and partually phenomenological study of human mind. We presume formal signs such as propositions and modal operators refer to mental states and can describe the general structure of mental activity. That is purely the approach of classical phenomenology – the study of experience and its structures. On the other hand the usage of formal logic is a classic analytic philosophy of mind. So the things are getting more complicated when taking in consideration that the initial framework of a study is analytic philosophy and not continental phenomenology. Phenomenology is of different intellectual and methodological tradition than any type of analytic philosophy including analytic philosophy of mind. From that stanpoint it may be said that paper is also interesting as a purely methodological project – it tries to find bridges between phenomenology and philosophy of mind. As for the action logics, mentalistic logic also studies rational behavior but does it on the other lever and often with a different purpose. The main problem in this case is philosophical interpretation of modality. Minor problems include shared content, many leveled self-referential structures and vagueness. The paper also studies brain in a vatt thought experiment as a methodological concept. The research will have implications for philosophy of logic, artificial intelligence and theory of reference.

Розглядаються філософські проблеми менталістської логіки. Менталістська логіка – це формальна система, яка концентрує увагу на закритих процесах ментального життя індивіду замість розгляду деяких зовнішніх деталей рацоінальної поведінки, як робить більшість логік, що існують (як, наприклад, BDI). Проект такої логіки порівнюється з логіками дії, що існують. Головна проблема в цьому розгляді – це проблема інтерпретації модальності. Менші проблеми містять загальнодоступний контент, багаторівневі структури, які посилаються самі на себе, а також нечіткість. Також досліджується мисленнєвий експеримент "мозок в бочці" як методологічний концепт. Це дослідження матиме наслідки для філософії логіки, штучного інтелекту, теорії референції.
Філософські проблеми менталістської логіки
Keywords: philosophy of logic; philosophy of mind; psychologistic logic; folk psychology; філософія логіки; філософія свідомості; психологістична логіка; народная психологія